Relieving exertional dyspnea during the 3-min constant speed shuttle test in patients with COPD with indacaterol/glycopyrronium versus tiotropium: the RED trial. (July 2020) - Beaulieu, Jessie; Jensen, Dennis; O'Donnell, Denis E.; Brouillard, Cynthia; Tracey, Lauren; Vincent, Sandra; Nadreau, Éric; Bernard, Emmanuelle; Bernard, Sarah; Maltais, François
Background: Exertional dyspnea is a cardinal feature of chronic obstructive pulmonary disease (COPD) and a major cause of activity limitation. Although dual bronchodilation is more effective than bronchodilator monotherapy at improving resting pulmonary function, it is unclear to which extent this translates into superior relief of exertional dyspnea. Methods: We conducted a randomized controlled, double-blind, cross-over trial comparing indacaterol 110 µg/glycopyrronium 50 µg once daily (OD) with tiotropium 50 µg OD in patients with moderate to severe COPD and resting hyperinflation (functional residual capacity >120% of predicted value). The primary outcome was Borg dyspnea score at the end of a 3-min constant speed shuttle test after 3 weeks of treatment. Secondary outcomes included changes in Borg dyspnea score after the first dose of study medication, expiratory flows and lung volumes. Statistical analysis was conducted using a cross-over analysis of variance model with repeated measurements. Results: A total of 50 patients with COPD and a mean forced expiratory volume in 1 s of 54 ± 11% (mean ± SEM) predicted participated in the cross-over phase of the trial. Compared with baseline, there was a decrease in dyspnea after the first dose of medication with indacaterol/glycopyrronium [mean −1.00, 95% confidence interval (CI) −1.49 to −0.52] but not with tiotropium alone (mean −0.36, 95% CI −0.81 to 0.08). The reduction in dyspnea after the first dose was statistically significant between the two treatments (mean difference of −0.64, 95% CI −1.11 to −0.17). Despite indacaterol/glycopyrronium providing further bronchodilation and lung deflation throughout the trial, the reduction in dyspnea was not sustained at 3 weeks of treatment (mean between-treatment difference at 3 weeks of 0.09, 95% CI −0.44 to 0.61). Conclusion: In comparison with bronchodilator monotherapy, indacaterol/glycopyrronium provided greater immediate exertional dyspnea relief, although this difference was not sustained after 3 weeks of therapy despite evidence of further bronchodilation and lung deflation. The reviews of this paper are available via the supplemental material section.